PRINCIPLES AND APPROACHES OF PSYCHOLOGICAL CORRECTION OF VICTIM BEHAVIOR OF ADOLESCENTS ON THE INTERNET (Psychology Travelogs, 2023)
This article examines the problem of victim behavior of modern teenagers on the Global Internet, which has a significant negative impact on their life and health, causing dangerous situations. Ukrainian researchers are actively studying victim behavior on the Internet, including online bullying, cybercrime, and other forms of electronic violence. They focus on the causes, consequences, and prevention strategies of these phenomena. The application of methodological approaches makes it possible to determine the problems of victimization of adolescents in social networks, to develop a strategy for solving them, and to create technological mechanisms for correcting the victim behavior of adolescents on the Internet. The article examines the approaches to the correction of adolescent victim behavior: axiological, systemic-personal, approach to the development of critical thinking, activity approach, health preservation approach and integrative approach. The axiological approach involves directing correctional work towards universal human values, a valuable attitude towards subjects of correction, and humane communication. The system-personal approach uses the individual resources of adolescents to achieve success in correcting their victim behavior. It is focused on the study of the individual as a subject of social security, its motivational relations, and social connections. The development of critical thinking involves the formation of teenagers' skills of independent judgment, working with information, and protection from negative influence on the Internet. The action-based approach aims to arm teenagers with the knowledge that they gain through hands-on activities and includes learning about victim behavior, cyberbullying, healthy lifestyles, and ways to counter the risks. Each of these approaches has its conceptual foundations and contributes to the effective correction of the victim behavior of adolescents on the Internet.The proposed article considers the principles of organizing correctional work regarding the victim behavior of teenagers on the Internet, based on the analysis of scientific and psychological-pedagogical literature: humanization, preemptiveness, social hardening, centering, health preservation, and integrativeness
Keywords: teenagers; victim behavior; approaches; psychological correction; Internet